APPLICATION OF PROJECT BASED LEARNING MODEL BASED ON ARTIFICIAL INTELLIGENCE (AI) TO IMPROVE CRITICAL SPATIAL THINKING OF STUDENTS IN SUKOHARJO REGENCY - Sriyanti Sriyanti; Chatarina Muryani; Singgih Prihadi (Universitas Sebelas Maret (UNS), 2026)
Project-Based Learning (PjBL) is a learning model that emphasises problem-solving through real-world activities and meaningful projects. The integration of Artificial Intelligence (AI) in PjBL is expected to enhance students’ engagement and higher-order thinking skills, particularly critical spatial thinking in geography learning. This study aims to improve students’ critical spatial thinking skills by applying an AI-based Project-Based Learning model to the topic of the dynamics of international cooperation. The research employed Classroom Action Research (CAR) conducted in three cycles—planning, action, observation, and reflection—during the even semester of the 2024/2025 academic year at State Senior High School 1 Sukoharjo. The research subjects were 35 students in Phase F+ / Grade XII. Data were collected using observation sheets, written tests (pretest and posttest), questionnaires, and documentation. Data analysis was carried out using descriptive qualitative analysis supported by quantitative data in the form of students’ learning achievement percentages based on critical spatial thinking indicators. The results showed a consistent improvement in students’ learning outcomes across the three cycles, with mastery learning increasing from 68.57% in cycle I to 77.14% in cycle II and reaching 91.43% in cycle III, exceeding the classical mastery criterion of 85%. The findings indicate that implementing AI-based PjBL effectively enhances students’ critical spatial thinking skills, learning motivation, and active participation. Therefore, AI-based Project-Based Learning can be considered a practical instructional approach to support meaningful, technology-integrated geography learning.